Augmenting the intangible: an intervention through an AR mobile app and an installation to foster a local cultural phenomenon - Prandi, Catia; Ceccarini, Chiara; Tumedei, Gianni; Salomoni, Paola (Frontiers in Computer Science, 2025)
IntroductionIn the context of preserving and promoting Intangible Cultural Heritage (ICH), we propose a technology-driven approach to transmit cultural and social phenomena to new generations. As a case study, we explored the umarell phenomenon, a deeply rooted tradition in the Emilia Romagna region, where retired men spend their time observing construction sites and offering unsolicited advice.MethodsOur intervention was designed using Human-Computer Interaction (HCI) methods, involving 15 young adults in a focus group and 73 participants in a survey. To engage digital natives in urban spaces, we developed an in-situ experience that combines tangible artifacts with interactive 3D digital content accessible through Augmented Reality (AR) on a mobile application. Our approach leverages smartphone sensors, including GPS and gyroscopes, to dynamically adjust and contextualize the 3D building model within the real environment, enhancing spatial awareness and immersion. To assess the effectiveness of our solution, we involved approximately 125 teenagers and young adults in a public demonstration.ResultsThe findings show that the umarell concept is more familiar to adults, who also recognize its territorial value, whereas younger participants were drawn primarily to the app's digital features (AR function and 3D model).DiscussionThis study extends existing research by showing how hybrid strategies, combining mobile AR with tangible elements, enhance engagement with cultural heritage among younger audiences. The intergenerational co-design process helped identify meaningful features while mitigating risks of cultural flattening and commodification. Overall, technology emerges not as a substitute but as a bridge for intergenerational cultural transmission.